CORRELATION BETWEEN KNOWLEDGE OF ADOLESCENT REPRODUCTIVE HEALTH WITH TEEN PREGNANCY PREVENTION - Ulfatul Latifah; Tatirah Tatirah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Risky sexual behavior among adolescents in various provinces increased due to the lack of knowledge about reproductive health. These problems impacted teen pregnancy, teen marriage, and high rates of abortion, which directly impact their reproductive health. This study aimed to determine the relationship between knowledge of reproductive health with teen pregnancy prevention. This research was observational with a cross-sectional approach. The population in this study were students of the Bakti Husada Brebes Vocational School. The sample was taken using purposive sampling and obtained from 40 people. Data collection through structured interviews using interview guidelines. Analysis data using Chi-square. The results show that respondents with excellent knowledge had good behavior in teen pregnancy prevention, while respondents with poor knowledge lacked in pregnancy prevention. The analysis shows a relationship between reproductive health and teen pregnancy prevention in adolescents (p-value of 0.046). It is hoped that adolescents can increase knowledge about reproductive health through appropriate information sources to prevent pregnancy at an early age.Keywords: knowledge, behavior, reproductive health